Houttuynia Essential Oil and its Self-Microemulsion Preparation Protect Against LPS-Induced Murine Mastitis by Restoring the Blood–Milk Barrier and Inhibiting Inflammation - Liu, Yuanyuan; Jiang, Yu; Yang, Yanfang; Wang, Hongliang; Ye, Jun; Liu, Dongdong; Chen, Yanmin; Lian, Chunfang; Wang, Renyun; Gao, Yue; Meng, Yingying; Gao, Lili; et al. (Frontiers in Immunology, 2022)
Mastitis is a common inflammatory disease caused by bacterial infection to the mammary gland that impacts human and animal health and causes economic losses. Houttuynia essential oil (HEO), extracted from Houttuynia cordata Thunb, exhibits excellent antibacterial and anti-inflammatory properties. The aim of the study was to investigate the effects of HEO and a self-microemulsion preparation of HEO (SME-HEO) on inflammation and the blood-milk barrier (BMB) in lipopolysaccharide-induced murine mastitis. HEO and SME-HEO significantly downregulated pro-inflammatory factors TNF-α and IL-1β, upregulated anti-inflammatory factor IL-10, inhibited MPO expression, and alleviated histopathological injury in murine mammary gland tissues. Additionally, HEO and SME-HEO protected the integrity of the BMB by upregulating the expression of junction proteins ZO-1, claudin-1, claudin-3, and occludin. The anti-inflammatory effect of HEO against murine mastitis was mediated by blocking the MAPK signaling pathway and expression of iNOS. By inhibiting the release of inflammatory factors and protecting the integrity of the BMB, HEO may provide a novel treatment for mastitis.